ANALISA PENGARUH STRUKTUR MODAL, PERPUTARAN ASET TERHADAP NILAI PERUSAHAAN PADA EMITEN BUMN SUBSEKTOR KONSTRUKSI DI BURSA EFEK INDONESIA PERIODE 2019 – 2021 - I KETUT KUSUMA WIJAYA (GANEC SWARA, 2023)
This research aims to investigate and analyse simultaneous and partial effects of debt equity ratio, asset turn over on value company at stated owned companies in subsector construction in Indonesia stock eschange. Sample of this research covers 4 out of 4 population listed construction companies in Indonesia Stock Exchange. Those samples have been selected using purposive sampling technique. This is a associative research using multiple linear regressions as an analysis method. Partially, only asset turn over effect the value of companies. Simultaneous test of multiple linear regressions indicates that debt equity ratio, asset turn over  perform significant effects on value company. The effect is 99,2 % and the rest 0,8 % has been affected by other factors.